In-hospital Mortality Reduction among Heart Failure Patients Treated with Optimal Dose of Angiotensin-Converting Enzyme Inhibitors - Yoseph Budi Utomo; Mohammad Saifur Rohman; Yoga Waranugraha; Djanggan Sargowo; Sasmojo Widito; Budi Satrijo; Setyasih Anjarwani (Heart Science Journal, 2020)
Background : Angiotensin-converting enzyme inhibitors (ACEI) should be titrated to the optimal dose for adequate inhibition of the Renin-Angiotensin-Aldosterone system (RAAS). The up-titration of ACEI to the optimal doses during in-hospital treatment is challenging.Objectives : This study aimed to investigate whether the use of optimal dose of ACEI during in-hospital treatment could give more benefit to the outcome of heart failure (HF) patients.Methods : We involved 171 HF patients in this prospective cohort study. 29 and 142 HF patients were treated with optimal dose and suboptimal dose of ACEI during in-hospital treatment, respectively. The primary endpoint was in-hospital and 30 days post-discharge mortality. The secondary endpoint was 30 days post-discharge rehospitalization due to worsening of HF.Results: Only 17% of HF patients treated with optimal dose of ACEI during in-hospital treatment. In-hospital mortality in optimal dose of ACEI group was lower than in suboptimal dose of ACEI group (0% vs. 19.7%; p = 0.009). The 30 days post-discharge mortality (0% vs 2.7%; p = 0.375) and rehospitalization (6.9% vs 16.7%; p = 0.184) between both groups were not significantly different.Conclusion: The use of optimal dose of ACEI during in-hospital treatment reduced in-hospital mortality in HF patients.